Space Consolidation for Fishing Settlement in Mariso District, Makassar City with Space Syntax - Andi Andre Pratama Putra; Ardhya Nareswari (Departement of Architecture, Universitas Islam Indonesia, 2019)
This paper discusses the development and changes in space that occur in the fishermen’s area of Panambungan fisheries in Mariso sub-district, along with the changes in space that occur as a result of reclamation activities and changes in spatial patterns around the fishing settlement area. Changes in the settlement’s spatial pattern show a trend of discrepancies between urban developments and the physical conditions of fishing settlement that can cause a decline in regional values. The study aims to get an overview of the current condition of the fishing settlement of Mariso and their changes based on the 2015-2034 spatial plan of Makassar city, and the consolidated directives that can be done. The results of this study are expected to be an input or a recommendation for Mariso fishing settlement in particular and the fishing settlement in Indonesia in general. The analysis process uses quantitative syntactic analysis with the help of Depthmap X computer software with descriptive quantitative method that is focused on consolidating the Mariso connection fisherman settlement. The results of the study show that the development of the city shows that the Mariso fisherman settlement spatial configuration based on the 2015-2034 Makassar City spatial plan has a better value of space analysis (integration, connectivity, mean of depth, choice and intelligibility), but there is a mismatch of physical spatial functions and patterns with existing fishing settlement. This is indicated by the occurrence of economic activity in the area (interaction), in which there is a change in space that does not support fisherman activities.Keywords: fishing settlement, space syntax, integration